The ryanodine receptor stabilizer S107 ameliorates contractility of adult Rbm20 knockout rat cardiomyocytes. Issue 17 (14th September 2021) - Guo, Wei; Zhu, Chaoqun; Yin, Zhiyong; Zhang, Yanghai; Wang, Chunyan; Walk, Andrea Sanchez; Lin, Ying‐Hsi; McKinsey, Timothy A.; Woulfe, Kathleen C.; Ren, Jun; Chew, Herbert G.
Abstract: RNA binding motif 20 (RBM20) cardiomyopathy has been detected in approximately 3% of populations afflicted with dilated cardiomyopathy (DCM). It is well conceived that RBM20 cardiomyopathy is provoked by titin isoform switching in combination with resting Ca 2+ leaking. In this study, we characterized the cardiac function in Rbm20 knockout (KO) rats at 3‐, 6‐, 9‐, and 12‐months of age and examined the effect of the ryanodine receptor stabilizer S107 on resting intracellular levels and cardiomyocyte contractile properties. Our results revealed that even though Rbm20 depletion promoted expression of larger titin isoform and reduced myocardial stiffness in young rats (3 months of age), the established DCM phenotype required more time to embellish. S107 restored elevated intracellular Ca 2+ to normal levels and ameliorated cardiomyocyte contractile properties in isolated cardiomyocytes from 6‐month‐old Rbm20 KO rats. However, S107 failed to preserve cardiac homeostasis in Rbm20 KO rats at 12 months of age, unexpectedly, likely due to the existence of multiple pathogenic mechanisms. Taken together, our data suggest the therapeutic promises of S107 in the management of RBM20 cardiomyopathy. Abstract : Loss of Rbm20 results in reduced myocardial stiffness at younger age and overt RBM20 cardiomyopathy at older age in rats. The RyR2 stabilizer S107 improves contractility properties by restoring the elevated resting intracellular Ca 2+ level in Rbm20‐depleted cardiomyocytes. S107 could be a component of a therapeutic option for RBM20 cardiomyopathy.